Relationship of cardiac troponin to systolic global longitudinal strain in hypertrophic cardiomyopathy. Issue 10 (28th August 2017) - Agarwal, Anushree; Yousefzai, Rayan; Shetabi, Kambiz; Samad, Fatima; Aggarwal, Saurabh; Cho, Chi; Bush, Michelle; Jan, M. Fuad; Khandheria, Bijoy K.; Paterick, Timothy E.; Tajik, A. Jamil
Abstract : Background: A high proportion of stable hypertrophic cardiomyopathy (HCM) patients have elevated serum cardiac troponin I (cTnI), but its clinical and echocardiographic determinants are unknown. Our objective was to determine the prevalence and clinical predictors of positive troponin (cTnI+) in a well‐defined population of HCM patients using a highly sensitive assay. Methods: We retrospectively interrogated medical records of 167 stable HCM patients from 1/2011 to 3/2014. cTnI >0.04 ng/mL was considered positive. Results: Thirty‐four percent were troponin‐positive (median cTnI was 0.1 [0.07, 0.2] ng/dL). cTnI as a continuous variable correlated positively with maximal left ventricular wall thickness (LVT), maximal interventricular septal thickness, and global longitudinal strain (GLS) ( P <.001). Unadjusted OR (95% CI) for positive troponin was 0.5 (0.3–0.9, P =.05) for obstructive HCM, 3.2 (1.7–5.9, P <.0001) for increased LVT, 0.3 (0.2–0.6, P <.0001) for −5% increase in GLS, 0.2 (0.04–0.9, P =.04) for moderate‐to‐severe mitral regurgitation, and 1.9 (0.9–3.9, P =.06) for implantable cardioverter defibrillator history. After adjusting for these variables, only maximum LVT (OR 2.5 [95% CI: 1.1–5.7, P =.02]) and GLS (OR 0.3 [95% CI: 0.2–0.6, P =.001]) were independent predictors. The percentage of patients with a positive cTnI increased from 19% to 24% and 57% across tertiles of LVT ( P =.003) and decreased from 54% to 33% and 14% across tertiles of GLS ( P <.0001). Conclusion: In this cohort of HCM patients, the association of reduced GLS and positive troponin was independent of LVT. Further studies are warranted to evaluate whether their combination adds prognostic value in identifying high‐risk patients to define effective and early intervention strategies.